DEFINIÇÃO DE UMA ARQUITETURA P2P BASEADA EM REPUTAÇÃO E ORIENTADA A SERVIÇOS - RAMOS, Flávio Marcílio Paiva (2009)
Nowadays, peer-to-peer networks are very popular mainly, when we wish to search or share a considerable amount of information and resources among various participants. One of the main difficulties of this technology is how to avoid that those participants maintain, at the same time, a considerable number of shared resources and to guarantee that those resources are not corrupted or polluted content. Another problem commonly found in P2P networks is the lack of interoperability among existing P2P solutions especially because the inconsistencies of metadata and operation interfaces used in node communication. This work describes P2PWSRep, a reputation management protocol that identifies non-cooperative nodes or that can hinder network performance by sharing corrupted, infected or non-existent files. P2PWSRep infrastructure was based on web services in order to tackle interoperability problems and to facilitate its extensibility, making it feasible to be accessed by several other P2P applications. The P2PWSRep protocol employs a distributed reputation computation using an exponentially weighted average that takes into account the current and previous node reputation and which is tuned by an adjustment parameter in order to obtain the final reputation, thus considering the node s behavior. The P2PWSRep protocol is validated by means of simulation and our results show that it is able to point out the more trustable nodes in the network as well as to insulate those which are not reliable or cooperative. Besides, the protocol does not unnecessarily impacts on the network load P2PWS.